Hubungan Pengeluaran Rumah Tangga, Asupan Protein, Dan Asupan Zat Besi Dengan Kadar Hemoglobin Pada Pekerja Tambang Pasir Tradisional - Syahid Kinayung Widyaji; Trias Mahmudiono (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2017)
Background: Anemia is one of the nutritional problem in society with low socioeconomic status. Low socioeconomic associated with lower nutritional intake do to limited access to a variety of foods.Objective: the aim of this study was to analyze the relationship netween household expenditure and intake protein with hemoglobin level among sand miner.Method: this was a cross sectional study with 51 sample sand miner was selected by simple random sampling. The data were collected through interview using questionnaire, 2x24 hours food recall, and hemoglobin level measured by Easy Touch GCHb. Data were analyzed using Pearson correlation.Result: The result showed that there were associations between household expenditure (p = 0.016) and intake protein (p = 0.037) to hemoglobin level. Conversely, there was no association between intakes of iron to hemoglobin level.Conclusion: Household expenditure and intake protein related to the hemoglobin level among sand miner.Conclusion : Patient satisfaction of food by outsourcing system was no difference from the patient satisfaction of food by self operated system.ABSTRAK Latar Belakang: Anemia merupakan salah satu masalah gizi pada masyarakat dengan status sosial ekonomi yang rendah. Pada sosial ekonomi yang rendah cenderung asupan zat gizinya rendah karena terbatasnya akses ke pangan yang beragam.Tujuan: Untuk menganalisis hubungan antara pengeluaran rumah tangga, asupan protein, dan asupan zat besi dengan kadar hemoglobin pada pekerja tambang pasir tradisional.Metode: Penelitian ini menggunakan desain cross sectional dengan besar sampel 58 pekerja tambang pasir tradisional yang dipilih menggunakan simple random sampling. Pengumpulan data dilakukan dengan wawancara menggunakan kuesioner, 2x24 hours food recall, dan kadar hemoglobin diukur dengan alat Easy Touch GCHb. Uji statistik yang digunakan adalah korelasi pearson.Hasil: Hasil penelitian menunjukkan terdapat hubungan pengeluaran rumah tangga (p = 0,016) dan asupan protein (p = 0,037) dengan kadar hemoglobin. Sebaliknya tidak terdapat hubungan asupan zat besi (p = 0,258) dengan kadar hemoglobin.Kesimpulan: Pengeluaran rumah tangga dan asupan protein berhubungan dengan kadar hemoglobin pada pekerja tambang pasir tradisional.